Library and information literacy among new intake of diploma students at Universiti Teknologi MARA (UiTM) Kedah / Raja Alwi Raja Omar … [et al.] - Raja Omar, Raja Alwi; Mohamed Sawal, Mohd Zool Hilmie; Azmi, Nor Azlina; Md. Radzi, Mohd Abdul Hafiz; Noordin, Nazni (Faculty of Information Management, 2013)
Malaysia is heading towards becoming an information and knowledge based society (K-Society). On-going efforts to establish our nation as a center of academic excellence are seriously being undertaken and those include reforming our educational system with the inclusion of personal skills development However, one skill that many in the education fraternity fail to see or unwittingly neglect is library and information skill among school students. Through general observations (by librarians) on students enrolled into institutions of higher learning (public or private), it can be assumed that majority of them do not possess understanding and skills in using the library and information or simply said, are library and information illiterate. This could be seen in their inability to correctly use or find library resources relevant to their information needs. Realizing this situation, a study was carried out by the researchers to provide evidence and proof to reaffirm this inadequacy which may become a great obstacle in moving towards becoming an information society. A survey questionnaire and also a set of library skills assessment questions were distributed to a new batch of students enrolled in the diploma programs at Universiti Teknologi MARA Kedah (UiTM Kedah). This batch of new students actually represents the Sijil Pelajaran Malaysia - SPM (and its equivalent) level school leavers. Their characteristics resemble other SPM school leavers who managed to further their studies at either other local or overseas universities and colleges, and also those who continued their daily lives outside the academic world. The focus of assessment was on library skills (for example bibliographic instruction). The outcome of the assessment indicated that a majority of UiTM Kedah students lack library skills and also most of the secondary school libraries or school resource centres lack in the provision of exposure on library skills to school students. As such, the question is what should be the plan to eradicate the problem that has been too long in existence?